Analisis Faktor-Faktor Yang Mempengaruhi Fluktuasi Harga Cabai Rawit Di Kabupaten Polewali Mandar - rahmat, rahmat; Hikmah, Aulia Nurul; Dambe, Jumriani; Hamsiah, Hamsiah; Ansyar, Ansyar; Hamsah, Hamsah (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
Cayenne pepper cultivation in Polewali Mandar Regency faces various challenges, one of which is price fluctuations in the market. The purpose of this study is to analyze the factors that influence the price fluctuations of cayenne pepper in Polewali Mandar Regency. The determination of the research location was carried out purposively, because Polewali Mandar Regency became one of the largest producers of cayenne pepper in West Sulawesi Province. The sample in this study was 40 samples. The analysis technique used is multiple linear regression analysis. The results of the research that have been carried out show that the factors that influence cayenne pepper price fluctuations, namely chili availability and demand for cayenne pepper, have a significant effect on cayenne pepper price fluctuations in Polewali Mandar Regency, while the price of cayenne pepper at the farm level and substitute goods have no significant effect on cayenne pepper price fluctuations in Polewali Mandar Regency.